Cytokeratin 17 is highly sensitive in discriminating cutaneous lymphadenoma (a distinct trichoblastoma variant) from basal cell carcinoma. (6th April 2016) - Goyal, Amrita; Solus, Jason F.; Chan, May P.; Doyle, Leona A.; Schaffer, Andras; Thakuria, Manisha; Horn, Thomas D.; Duncan, Lyn M.; Nazarian, Rosalynn M.
Abstract : Background: Cutaneous lymphadenoma (CL) is rare neoplasm that clinically and histologically resembles basal cell carcinoma (BCC). CL, composed of dermal basaloid epithelial islands with prominent admixed lymphocytes, characteristically contains cytokeratin 20 (CK20)‐positive Merkel cells (MCs). However, CK20 may be of limited use because of low MC density in small samples. CK17 is expressed diffusely throughout BCC. We investigated the discriminatory utility of CK17 and CK20 in CL and BCC. Methods: A retrospective clinicopathological review of 11 cases of CL and 14 BCC was performed. CK20‐positive MCs within basaloid tumor lobules and CK17 immunohistochemical staining and pattern of expression were recorded. Results: Intratumoral CK20‐positive MCs were identified in 4/11 CL cases (36.4%) and 0/14 BCC cases (p = 0.012, sensitivity = 0.36). CK17 showed diffuse positive staining in all 14 BCC cases. CK17 showed a distinct patchy and peripheral rim staining in basaloid islands of 10/11 CL cases (p < 0.001, sensitivity = 0.91); one case showed patchy staining throughout tumor lobules. Conclusions: In cases with a differential diagnosis of CL and BCC, CK20 staining of intratumoral MCs has a high positive predictive value for CL but is of low sensitivity. The pattern of CK17 expression is a highly sensitive marker for distinguishing CL from BCC in small samples.